Experimental warming causes large yield reduction of spring highland barley, and the changes of the phyllosphere microbial community represents the extrinsic manifestation of the underlying mechanism - Zhiming Zhong; Guangyu Zhang; Gang Fu (PLoS ONE, 2025)
Changes in phyllosphere microbial communities of highland barley caused by climate warming (e.g., increases in the abundance of pathogenic fungi) is a potential important mechanism leading to the decrease in yield of highland barley. However, there are no reports that the loss of highland barley yield caused by climate warming is attributed to changes in phyllosphere microbial community of the highland barley. Here, based on a field warming experiment in the Lhasa city, Tibet, we examined the responses of phyllosphere bacterial and fungal communities to warming and their feedbacks to the yield of spring highland barley. Warming decreased yield of highland barley by 34.04%, but increased soil temperature by 2.40°C, phyllosphere fungi species richness by 50.00%, fungi Chao1 by 37.55%, fungi phylogenetic diversity by 51.74%, and pathotroph fungi by 529.17%. Yield of highland barley decreased with increasing phyllosphere fungi species richness, fungi Chao1, fungi phylogenetic diversity and pathotroph fungi. Warming altered phyllosphere bacterial functional composition, which was also marginally correlated with yield of highland barley. Moreover, warming only caused the forward shift of each phenology, and did not change the time interval between the two adjacent phenological periods. The change of phyllosphere microbial community, especially fungal community, caused by warming is a potentially important mechanism leading to the yield reduction of highland barley, which provides a new perspective for the regulatory mechanism of highland barley yield reduction and even grain yield reduction under future climate warming. More importantly, the scientific findings of this study may provide potential new directions (e.g., exogenous addition of beneficial phyllosphere microbial fertilizers) on how to mitigate grain yield reduction caused by climate warming.